1994
DOI: 10.1210/jcem.78.4.8157723
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal 11 beta-oxidation of 9 alpha-fluorocortisol: an explanation for its mineralocorticoid potency.

Abstract: 9 alpha-Fluorocortisol (9 alpha FF) is about 200 times more potent as a mineralocorticoid than cortisol (F) in man, although it binds with the same affinity as F and aldosterone to the human mineralocorticoid receptor. The low mineralocorticoid activity of F has been shown to be due to its rapid conversion by the kidney to cortisone (E), which does not bind to the receptor. Therefore, we compared the conversion of F to E with that of 9 alpha FF to 9 alpha-fluorocortisone (9 alpha FE) by 11-hydroxysteroid dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Depending on their chemical structure, they display pharmacological profiles different from those of the naturally occurring glucocorticoids. This can be explained in part by their different metabolic properties, as for example in the case of 9α‐fluorinated GCs [22, 23]. We therefore studied the metabolism and inhibitor characteristics of commonly used synthetic systemic and topical GCs with the recombinant type 1 enzyme, allowing us to draw conclusions concerning the active site architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their chemical structure, they display pharmacological profiles different from those of the naturally occurring glucocorticoids. This can be explained in part by their different metabolic properties, as for example in the case of 9α‐fluorinated GCs [22, 23]. We therefore studied the metabolism and inhibitor characteristics of commonly used synthetic systemic and topical GCs with the recombinant type 1 enzyme, allowing us to draw conclusions concerning the active site architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to assess the effect of hydrocortisone replacement on cardiovascular function in patients with hypopituitarism and its results have been reported (Dunne et al, 1995). All patients were fully replaced, where appropriate, with other endocrine drugs (thyroxine, sex steroids and DDAVP), but no patient received GH or fludrocortisone, each of which may alter cortisol metabolism (Weaver et al, 1994;Oelkers et al, 1994). Patients had been taking the above doses of hydrocortisone for at least 3 months prior to the urine collection.…”
Section: Patients With Hypopituitarismmentioning
confidence: 99%
“…Astonin HR) is used for mineralocorticoid (MC) substitution in patients with Addison's disease. In experiments with human kidney slices, we have shown that its high MC potency compared to unfluorinated cortisol is due to decreased renal oxidation (inactivation) and increased renal reduction of the 11-oxo steroid [40]. As these studies did not prove which isoenzyme was responsible for the unexpected renal reductase activity, we did further experiments with dexamethasone (D), an often used 9␣-fluorinated GC.…”
Section: Synthetic Steroids and Their Metabolism By 11␤-hsd-iimentioning
confidence: 99%